2020
DOI: 10.1101/2020.10.29.361329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional profiling reveals conserved and species-specific plant defense responses during the interaction of the early divergent plantPhyscomitrium patenswithBotrytis cinerea

Abstract: Bryophytes were among the first plants that colonized earth and they evolved key defense mechanisms to counteract microbial pathogens present in the new environment. Although great advances have been made on pathogen perception and subsequent defense activation in angiosperms, limited information is available in early divergent land plants. In this study, a transcriptomic approach uncovered the molecular mechanisms underlying the defense response of the bryophyte Physcomitrium patens against the important plan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 101 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Several secreted enzymes of B. cinerea are recognized by plant leucine-rich repeat receptors, including PGs [ 93 ], and BcXYG1 [ 42 ], leading to activation of plant defense. Interestingly, P. patens induces rapidly the expression levels of a high number of genes encoding these type of receptors during B. cinerea infection [ 28 ]. However, further research is needed to understand if some of these receptors recognize PGs and other fungal PAMPs in moss tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several secreted enzymes of B. cinerea are recognized by plant leucine-rich repeat receptors, including PGs [ 93 ], and BcXYG1 [ 42 ], leading to activation of plant defense. Interestingly, P. patens induces rapidly the expression levels of a high number of genes encoding these type of receptors during B. cinerea infection [ 28 ]. However, further research is needed to understand if some of these receptors recognize PGs and other fungal PAMPs in moss tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, further research is needed to understand if some of these receptors recognize PGs and other fungal PAMPs in moss tissues. Moreover, we observed that two genes encoding putative plant pectin methyl-esterase inhibitor were upregulated in P. patens after B. cinerea colonization [ 28 ]. These inhibitors could be involved in making the wall more resistant to degradation by fungal enzymes by increasing methylated pectin in the cell wall [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weisshaar and Jenkins 1998, Deluc et al 2006, Xie et al 2008). PAL genes are responsive to biotic stressors (Oliva et al 2015, Reboledo et al 2021). It is therefore, in general, not surprising that genes from the phenylpropanoid pathway are responsive to the treatment.…”
Section: Resultsmentioning
confidence: 99%